2007
DOI: 10.1016/j.brainres.2006.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid biomarkers showing neurodegeneration in dogs with GM1 gangliosidosis: Possible use for assessment of a therapeutic regimen

Abstract: gangliosidosis and preliminarily evaluated the efficacy of long-term glucocorticoid therapy for GM1 gangliosidosis using the biomarkers identified here. GM1 gangliosidosis, a lysosomal storage disease that affects the brain and multiple systemic organs, is due to an autosomal recessively inherited deficiency of acid β-galactosidase activity. Pathogenesis of GM1 gangliosidosis may include neuronal apoptosis and abnormal axoplasmic transport and inflammatory response, which are perhaps consequent to massive neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
32
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 45 publications
4
32
0
2
Order By: Relevance
“…In humans, there is evidence that the NSE concentration in the CSF rises with age [18]. In the previous report, the dogs were 1-13 months old [14]. In the present study, the age of the healthy dogs was 2-9 years old with an average age of 4.9 ± 2.8 years old.…”
Section: Discussionsupporting
confidence: 48%
See 2 more Smart Citations
“…In humans, there is evidence that the NSE concentration in the CSF rises with age [18]. In the previous report, the dogs were 1-13 months old [14]. In the present study, the age of the healthy dogs was 2-9 years old with an average age of 4.9 ± 2.8 years old.…”
Section: Discussionsupporting
confidence: 48%
“…However, many of the proteins in canine CSF that we identified after centrifugal filter desalting have been identified in 2DE studies in humans and other animals [2,7,8]. Neuron-specific enolase (NSE) is known as a biomarker of CNS disorders, for example, ischemia, head trauma, spinal cord injury and some of tumors, in humans [3, 6, 9, 12, In present study, the concentration of NSE of healthy dogs was higher than that found in a previous report [14]. This is likely due to the difference in methodology and age of the control group.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Other researchers have not found CSF CK activity to be a useful determinant of disease status or outcome in humans 17 or horses. 18 In humans with head trauma, 19 CSF AST activity has been associated with lesion severity, and in dogs, 20 it has been detected in individuals with degenerative diseases of the CNS.…”
mentioning
confidence: 99%
“…Cerebrospinal fluid (CSF) has been investigated as a potential source of biomarkers in a range of human and animal neurological disorders (Satoh et al 2007;Tumani et al 2008). From a veterinary perspective, a number of neurological conditions can present similar clinical features and therefore the identification of specific biomarkers would greatly facilitate diagnosis, patient treatment and management strategies.…”
Section: Introductionmentioning
confidence: 99%